India's Banks : Lending to Productive Firms? - George, Siddharth (IMF Working Papers; Working Paper ;, 2022)
Capital misallocation is widely thought to be an important factor underpinning productivity and income gaps between advanced and emerging economies. This paper studies how well Indian banks allocate capital across firms with varying levels of productivity. The analysis reveals that the link between productivity and bank credit growth is weaker for firms with significant ties to public sector banks, especially in years when public sector banks represent a large share of new credit. Large flows of credit to unproductive firms represent important missed growth opportunities for more productive firms. These results suggest that measures to improve governance of public sector banks, potentially including privatization, would help reduce capital misallocation.